TLR7/8 regulates type I and type III interferon signalling in rhinovirus 1b-induced allergic asthma - Krug, Jasmin; Kiefer, Alexander; Kölle, Julia; Vuorinen, Tytti; Xepapadaki, Paraskevi; Stanic, Barbara; Chiriac, Mircea-Teodor; Akdis, Muebeccel; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Finotto, Susetta (European Respiratory Journal, 2021)
Introduction: Interferon (IFN) responses have been reported to be defective in rhinovirus (RV)-induced asthma. The heterodimeric receptor of type I IFN (IFN-α/β) is composed of IFN-αR1 and IFN-αR2. Ligand binding to the IFN-α/β receptor complex activates signal transducer and activator of transcription (STAT) proteins STAT1 and STAT2 intracellularly. Although type III IFN (IFN-λ) binds to a different receptor containing IFN-λR1 and interleukin-10R2, its triggering leads to activation of the same downstream transcription factors. Here, we analysed the effects of RV on IFN type I and III receptors, and asked about possible Toll-like receptor 7/8 (TLR7/8) agonist R848-mediated IFN-αR1 and IFN-λR1 regulation. Methods: We measured IFN-α, IFN-β and IFN-λ and their receptor levels in peripheral blood mononuclear cell (PBMC) supernatants and cell pellets stimulated with RV1b and R848 in two cohorts of children with and without asthma recruited at pre-school age (PreDicta) and at primary school age (AGENDAS) as well as in cell supernatants from total lung cells isolated from mice. Results: We observed that R848 induced IFN-λR mRNA expression in PBMCs of healthy and asthmatic children, but suppressed IFN-αR mRNA levels. In murine lung cells, RV1b alone and together with R848 suppressed IFN-αR protein in T-cells compared with controls and in total lung IFN-λR mRNA compared with RV1b infection alone. Conclusions: In PBMCs from pre-school age children, IFN-αR mRNA was reduced and IFN-λR1 mRNA was induced upon treatment with the TLR7/8 agonist R848, thus suggesting new avenues for induction of antiviral immune responses in paediatric asthma.
CRIS-Team Scopus Importer:2021-06-04